THE IMPACT OF ARTIFICIAL INTELLIGENCE IN THE WORKPLACE: OPPORTUNITIES, CHALLENGES, AND THE REDEFINITION OF PROFESSIONAL SKILLS - Fikri, Maiza; Eriska, Marta (PT. Hafasy Dwi Nawasena, 2026)
This article examines how Artificial Intelligence (AI) is fundamentally transforming the workplace by creating new opportunities, intensifying challenges, and redefining professional skills. The background of the study arises from the rapid integration of AI into organizational systems, which alters job structures, workflow patterns, and human roles in decision-making processes. This study employs a qualitative library research design by analyzing recent accredited journal sources discussing AI adoption, workforce dynamics, and emerging skill frameworks. Data were collected through systematic documentation and analyzed using thematic content analysis to identify patterns related to opportunity–risk dynamics and skill redefinition in AI-driven environments. The findings reveal that AI generates new job categories, increases productivity, and supports innovative work models such as human–AI collaboration, while also causing job displacement, skill mismatch, inequality, and psychosocial pressure. The discussion highlights the necessity of hybrid professional competencies, combining digital and AI literacy, transversal skills, and ethical oversight capabilities. In conclusion, sustainable adaptation to AI requires continuous upskilling and reskilling ecosystems supported by organizations and policymakers to ensure AI becomes an enabler of human advancement rather than a source of exclusion